Evidence of Systemic Cytokine Release in Patients Undergoing Cardiopulmonary Bypass - Halter, Jeffrey (J Extra Corpor Technol, 2005)
Cardiopulmonary bypass (CPB) causes a systemic inflammatory response syndrome (SIRS), which can progress to an acute lung inflammation known as postperfusion syndrome. We developed a two-phase hypothesis: first, that SIRS, as indicated by elevated cytokines post-CPB, would be correlated with postoperative pulmonary dysfunction (Phase I), and second, that the cytokine interleukin-6 (IL-6) is predominantly released from the heart in CPB patients (Phase II). Blood samples were collected from patients undergoing CPB for elective cardiac surgery. In seven patients (Phase I), arterial samples were drawn before, during (5 minutes and 60 minutes), and after CPB. In 14 patients (Phase II), samples were collected from the coronary sinus, superior vena cava, and a systemic artery at the times indicated previously. Samples were analyzed with enzyme-linked immunosorbent assay: IL-1, IL-6, IL-8, IL-10, and tumor necrosis factor-α were assessed in Phase I and IL-6 assessed in Phase II. In Phase I, IL-6, IL-8, and IL-10 were elevated after CPB, but only IL-6 concentrations correlated with lung function. In summary, Phase I data demonstrate that increased IL-6 levels at the end of CPB correlate with reduced lung function postoperatively. In Phase II, IL-6 elevation was similar at all sample sites suggesting that the heart is not the major source of IL-6 production. We suggest that IL-6 be implemented as a prognostic measure in patient care, and that patients with elevated IL-6 after CPB be targeted for more aggressive anti-inflammatory therapy to protect lung function.